Veterinary treatment of sheep and goats [ - Duncanson, Graham R. (CABI, 2012)
Sheep and goats are farmed worldwide for meat, milk, skins and wool. This diverse range of uses means that many people rely on these animals as a source of income, food and warm clothing, though they can also be kept as pets. This book provides a genera veterinary guide to treating common conditions in these animals